Ultrasound measurements of rectus femoris and locomotor outcomes in patients with spinal cord injury - Tay, Matthew Rong Jie (2023)
Patients with incomplete spinal cord injury have decreased mobility, and many do not recover walking ability. The purpose of this study was to investigate rectus femoris muscle thickness and echo intensity on ultrasound and functional outcomes in these patients. This was a prospective cohort study in an inpatient rehabilitation center, which recruited 40 consecutive patients with incomplete spinal cord injury. The patients underwent an ultrasound assessment at 6 weeks post-injury. Ultrasound measurements were performed using B-mode ultrasound scanning and standardized protocols. Functional outcomes on discharge, including Lower Extremity Muscle Score (LEMS), Functional Independence Measure (FIM), and Walking Index for Spinal Cord Injury II (WISCI II), were measured. Rectus femoris muscle thickness was significantly correlated with discharge LEMS (Spearman’s rho = 0.448; p = 0.004), FIM motor subscale (Spearman’s rho = 0.595; p < 0.001), FIM walk subscale (Spearman’s rho = 0.621; p < 0.001) and WISCI II (Spearman’s rho = 0.531; p < 0.001). The rectus femoris echo intensity was also significantly correlated with discharge LEMS (Spearman’s rho = −0.345; p = 0.029), FIM motor subscale (Spearman’s rho = −0.413; p = 0.008), FIM walk subscale (Spearman’s rho = −0.352; p = 0.026), and WISCI II (Spearman’s rho = −0.355; p = 0.025). We report that a relationship exists between rectus femoris muscle ultrasonographic characteristics and muscle function and ambulatory outcomes after inpatient rehabilitation. Ultrasound muscle measurements are potentially useful in assessing muscle wasting and function in patients with spinal cord injury.